Web-Based Geographic Information System to Find Viral Culinary Tourist Spots - Supiyandi, Supiyandi; Binti Mailok, Ramlah (International Journal of Advances in Data and Information Systems, 2024)
The development and implementation of a Web-Based Geographic Information System (GIS) designed to help users discover viral culinary tourist spots, focusing on promoting local food culture. The system is built using the PHP programming language, leveraging its robust server-side scripting capabilities for dynamic web development. The GIS platform integrates various functionalities, including real-time mapping, geolocation services, and user-generated content, to offer an interactive experience for tourists. The platform allows users to search for culinary hotspots, view their locations on an interactive map, get directions, and read reviews from other users. Business owners can register and update information about their culinary spots, contributing to an up-to-date, community-driven database. The system employs a MySQL database to store location data, user profiles, and reviews, while Google Maps API is used for map visualization and geolocation services. The backend structure is built to handle high-traffic environments, using PHP's object-oriented features for efficient and scalable code management. Administrators can moderate content, ensuring the reliability and quality of the information provided. Implementing this system in PHP highlights the language’s flexibility in creating web-based GIS platforms, demonstrating how culinary tourism can be enhanced through modern web technologies. This paper discusses the technical aspects of the system’s architecture, database management, and frontend-backend integration, offering insights into the benefits of using PHP for developing similar GIS applications.